Importance of paraoxonase 1 (PON1) as an antioxidant and antiatherogenic enzyme in the cardiovascular complications of type 2 diabetes: Genotypic and phenotypic evaluation. (March 2020) - Shokri, Yasaman; Variji, Atena; Nosrati, Mani; Khonakdar-Tarsi, Abbas; Kianmehr, Anvarsadat; Kashi, Zahra; Bahar, Adele; Bagheri, Abouzar; Mahrooz, Abdolkarim
Graphical abstract: Abstract: Oxidant–antioxidant imbalance is involved in the etiology of different diseases, including cardiovascular diseases (CVDs), liver disorders, kidney diseases, cancers and diabetes mellitus. Antioxidant enzymes play a key role in striking an oxidant–antioxidant balance. Moreover, paraoxonase 1 (PON1) is an antioxidant enzyme that binds with high-density lipoprotein (HDL) in the circulation, and antioxidant and antiaterogenic properties of this lipoprotein are significantly associated with PON1. Research suggests PON1 contributes to the pathogenesis of certain human diseases such as type 2 diabetes (T2D). The association between PON1 and T2D appear to be reciprocal so that the disease significantly decreases PON1 levels and in turn, the genetics of PON1 may have a role the risk of susceptibility to T2D. Several factors that reduce the activity and concentration of PON1 in patients with T2D include increased glycation and loss-of-function polymorphisms. The genotypic and phenotypic evaluations of PON1 are therefore crucial for assessing the risk of cardiovascular complications in these patients, and strategies for increasing or restoring PON1 levels are useful for reducing or preventing their cardiovascular complications as their main cause of mortality. The present review aimed at discussing and emphasizing the key role of PON1 in T2D as a silent and dangerous disease.